Micro-structural analysis of NiFe2O4 nanoparticles synthesized by thermal plasma route and its suitability for BSA adsorption - Bhosale, Shivaji V.; Kanhe, Nilesh S.; Bhoraskar, S. V.; Bhat, Suresh K.; Bulakhe, Ravindra N.; Shim, Jae-Jin; Mathe, Vikas L. (Journal of Materials Science-Materials in Medicine, 2015)
The paper presents the experimental studies pertaining to the adsorption of bovine serum albumin (BSA) on the nanoparticles of nickel ferrite (NiFe2O4) with a view of correlating the adsorption properties to their microstructure and zeta potentials. Physical properties of two kinds of nickel ferrites, one synthesized by thermal plasma route and the other by chemical co-precipitation method, are compared. Maximum adsorption (231.57 lg/mg) of BSA onto nickel ferrite nanoparticles, at body temperature (37 degrees C) was observed at pH-value of 5.58 for the thermal plasma synthesized particles showing its higher adsorption capacity than those synthesized by wet chemical means (178.71 mu g/mg). Under the same physical conditions the value of zeta potential, obtained for the former, was higher than that of the latter over a wide range of pH values (3.64-9.66). This is attributed to the differences in the specific surface energies of the two kinds of nanoparticles arising from the degree of crystallinity. The paper presents the experimental evidence for the single crystalline nature of the individual nanoparticles, with mean size of 32 nm, for the thermal plasma synthesized particles as evidenced from the high resolution transmission electron microscopy and electron diffraction analysis. The measurements also reveal the poor crystalline morphology in the chemically prepared particles (mean size of 28 nm) although the X-ray diffraction patterns are not much different. The atomic force microscopy images confirm that the surfaces of plasma synthesized nanoparticles possesses higher surface roughness than that of chemically synthesized one. Presence of adsorbed protein was confirmed by vibrational spectroscopy. The Langmuir adsorption model is found to fit into the experimental data better than the Freundlich adsorption model.

Field emission performance of 2D Ti2CT x (T x = O2, F2, O-F) MXene: experimental insights and theoretical endorsement - Kakade, Prashant M.; Aher, Rahul; Kachere, Avinash R.; Cho, Jinill; Deore, Amol; Jadkar, Sandesh R.; Chauhan, Inderjeet; Kim, Taesung; Mandlik, Nandkumar T.; Kim, Ji Man; Bulakhe, Ravindra N. (ACS Applied Nano Materials, 2026)
Field emission (FE) is an important electron emission mechanism for vacuum microelectronic devices; however, conventional emitters often exhibit high turn-on fields, limited emission stability, and degradation during prolonged operation. Two-dimensional MXenes have recently emerged as promising FE materials due to their remarkable electrical conductivity, comparatively low work function, and tunnelable surface terminations. Nevertheless, most studies have focused on Ti3C2T x MXene, while other compositions such as Ti2CT x remain largely unexplored, particularly regarding the influence of surface terminal groups on their electronic and emission properties. Herein, Ti2CT x (T x = -F2, -O2, -OF) MXene was synthesized via selective chemical etching of the Ti2AlC MAX phase and investigated for its FE characteristics. The material exhibits a polycrystalline hexagonal layered structure with a high specific surface area of 349.02 m2 g-1. Ti2CT x MXene demonstrates excellent FE performance with a low turn-on field of 1.56 V mu m-1 and a threshold field of 2.0 V mu m-1 (at 10 mu A cm-2), along with a stable emission for 4 h. Density functional theory calculations further reveal that surface terminations strongly influence the electronic structure and work function, with the experimental value of 4.66 eV closely matching the -F2 termination. These results highlight Ti2CT x MXene as a promising material for stable and efficient FE applications.
Keywords: 2D Ti2CT x MXene; field emission; TDOS and PDOS; Turn-on voltage; Work function